Review of Management Flow and Risk Factors of Dehydration in Hajj Pilgrims at the Surabaya Debarkation Hajj Dormitory: a case report - A’yuni Syukri, Nur Alqurratu; Khairunisa, Luthia; Christiadji, Christiadji; Rachmawati, Ermin (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v2i0.3302, 2025)
This study evaluates the management protocols and risk factors for dehydration among Hajj pilgrims at the Surabaya Hajj Debarkation Dormitory, Indonesia, where extreme heat, physical exertion, and logistical challenges heighten health risks. Through observational data, medical records, a case analysis of a 98-year-old pilgrim with severe dehydration, the research identifies key risk factors: advanced age, chronic diseases (e.g., diabetes, hypertension), environmental extremes, inadequate fluid intake, and limited health literacy. The study outlines a structured management flow, emphasizing early screening upon arrival, rapid intravenous rehydration (normal saline/Ringer’s lactate) for critical cases, and oral rehydration therapy (ORS) for stabilization. Medical staff play a critical role in symptom detection, emergency interventions, and educating pilgrims on hydration practices. Challenges such as delayed symptom recognition, vascular access difficulties in dehydrated patients, and resource limitations underscore the need for standardized protocols and enhanced training. Recommendations include improving pre-departure education on hydration, strengthening medical response capabilities, and ensuring accessible rehydration resources. These measures aim to reduce dehydration-related complications, optimize care during debarkation, and safeguard pilgrim health in high-risk environments. The findings highlight the urgency of interdisciplinary collaboration and systemic improvements to address dehydration risks effectively in large-scale religious gatherings.